Efficacy of PRECICE Nail in Treatment of Adult Patients With Posttraumatic Femoral Leg Length Discrepancy. Issue 8 (August 2021) - Brinker, Mark R.; Amirian, Aslan; O'Connor, Daniel P.; Laughlin, Mitzi S.
Abstract : Summary: Posttraumatic, limb length discrepancy in adults is a challenge to treat, and multiple treatment protocols over the years have shown varying levels of success and complications. Before the introduction of the PRECICE nail in 2011, our preferred method of limb lengthening used an Ilizarov or Taylor Spatial frame. To assess the PRECICE nail, we evaluated the accuracy and complications during treatment in a series of skeletally mature patients with posttraumatic femoral limb length discrepancy. The surgical technique along with a case series of 8 patients are described in detail. On average, the target lengthening for the PRECICE nail was 44 mm, and all patients achieved lengthening within 2 mm and complete bony consolidation. The only observed complication in our series was a broken screw 1 year after the patient started weight-bearing. The PRECICE nail demonstrated promising results and was useful for bone regeneration and consolidation without the need for additional procedures. The rate of complications was low compared with previous methods, making this device an excellent treatment option.